2017
DOI: 10.1002/marc.201700203
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic‐Mediated Alternating Radical Copolymerization of tert‐Butyl‐2‐Trifluoromethacrylate with Vinyl Acetate and Synthesis of Block Copolymers Thereof

Abstract: Organometallic-mediated radical polymerization (OMRP) has given access to well-defined poly(vinyl acetate-alt-tert-butyl-2-trifluoromethacrylate)-b-poly(vinyl acetate) and poly(VAc-alt-MAF-TBE) copolymers composed of two electronically distinct monomers: vinyl acetate (VAc, donor, D) and tert-butyl-2-trifluoromethacrylate (MAF-TBE, acceptor, A), with low dispersity (≤1.24) and molar masses up to 57 000 g mol . These copolymers have a precise 1:1 alternating structure over a wide range of comonomer feed composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 54 publications
5
17
0
Order By: Relevance
“…It is noted that the temperatures used for these polymerizations are equivalent or lower than that of the corresponding VDF polymerizations (i.e., up to 80 • C with compound 3 in entry 4, vs. 100 • C for the VDF polymerization). The 1 H and 19 F NMR spectra ( Figures S20 and S21, respectively) of the isolated copolymer ( Table 5, entry 4) are in agreement with the previously published ones [42,44] and clearly show the perfect alternation of comonomers since no 1 H NMR signal centered at δ 4.9 ppm (the typical chemical shift of VAc-VAc dyads) was observed.…”
Section: Entry Activation Methods Reaction Time (H) Yield a (%) Mn B (supporting
confidence: 88%
See 1 more Smart Citation
“…It is noted that the temperatures used for these polymerizations are equivalent or lower than that of the corresponding VDF polymerizations (i.e., up to 80 • C with compound 3 in entry 4, vs. 100 • C for the VDF polymerization). The 1 H and 19 F NMR spectra ( Figures S20 and S21, respectively) of the isolated copolymer ( Table 5, entry 4) are in agreement with the previously published ones [42,44] and clearly show the perfect alternation of comonomers since no 1 H NMR signal centered at δ 4.9 ppm (the typical chemical shift of VAc-VAc dyads) was observed.…”
Section: Entry Activation Methods Reaction Time (H) Yield a (%) Mn B (supporting
confidence: 88%
“…Four copolymerizations of vinyl acetate (VAc) and tert-butyl 2-(trifluoromethyl)acrylate (MAF-TBE) were carried out using compounds 3 and 6 as initiators (Scheme II). This copolymer was previously synthesized by conventional [41] OMRP using cobalt(II) acetylacetonate as a controlling agent [42] and RAFT polymerization [43]. All these four co-polymerizations led to copolymers, which display a perfectly alternating structure, in agreement with the measured reactivity ratios that are both close to zero [41].…”
Section: Radical Polymerization Of Vdf With 2 3 and 5 As Initiatorsupporting
confidence: 69%
“…Indeed, the isolated polymers had higher molar masses, according to the SEC analyses (Table S1), than predicted for a controlled polymerization. Attempts to obtain a homopolymer from MAF-TBE in the presence of 3 failed as expected, since this monomer does not homopolymerize under radical conditions [35,36].…”
Section: Resultsmentioning
confidence: 87%
“…Its performances in the bulk polymerization of VAc and in the bulk copolymerization of VAc and tert -butyl 2-trifluoromethylacrylate (MAF-TBE) are evaluated here. The combination of these two monomers was recently shown to radically polymerize in a strictly alternating fashion (their reactivity ratios are essentially zero) [34] and to be well controlled by Co(acac) 2 [35]. Fluorinated copolymers containing 2-(trifluoromethyl)acrylic acid (MAF) and alkyl 2-trifluoromethacrylates (MAF-esters) may have applications in molecularly imprinted polymers, microlithography, polymer gel electrolyte membranes for fuel cells, and polymer electrolytes for Li-ion batteries [36].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ameduri et al reported another case in [35], where an organometallically mediated radical polymerization of VDF with an organocobalt compound R 0 (VAc) n Co III (acac) 2 (R 0 = primary radical generated by V-70, n ≈ 4) as initiator was achieved. Besides these, there were also some studies reporting the cobalt-mediated radical copolymerization of fluorinated monomers and VAc in the last two years [36,37,38]. However, the fluorinated monomers used in these works have no fluorine atom on the double bond, meaning that they have very similar chemical properties with non-fluorinated monomers.…”
Section: Introductionmentioning
confidence: 99%